2001
DOI: 10.1073/pnas.071067198
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the role of phosducin: Light-regulated binding of phosducin to 14-3-3 in rod inner segments

Abstract: Phosducin (Pd), a small protein found abundantly in photoreceptors, is widely assumed to regulate light sensitivity in the rod outer segment through interaction with the heterotrimeric G protein transducin. But, based on histochemistry and Western blot analysis, Pd is found almost entirely in the inner segment in both light and dark, most abundantly near the rod synapse. We report a second small protein, 14-3-3, in the rod with a similar distribution. By immunoprecipitation, phospho-Pd is found to interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 44 publications
11
49
0
Order By: Relevance
“…First, the localization of Pdc and G t βγ in photoreceptors has been measured more carefully, both by immunohistochemistry [45,46] and by microtome sectioning [19]. These studies have shown that Pdc localization does not mimic that of G t βγ.…”
Section: Modifying the Model -New Clues About Pdc Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the localization of Pdc and G t βγ in photoreceptors has been measured more carefully, both by immunohistochemistry [45,46] and by microtome sectioning [19]. These studies have shown that Pdc localization does not mimic that of G t βγ.…”
Section: Modifying the Model -New Clues About Pdc Functionmentioning
confidence: 99%
“…These studies have shown that Pdc localization does not mimic that of G t βγ. Pdc is found throughout the rod photoreceptor cell, from the outer segment to the inner segment and synaptic terminus [19,45,46]. Moreover, its distribution doesn't change in response to light.…”
Section: Modifying the Model -New Clues About Pdc Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pdc is found in all compartments of the photoreceptor cell, with a distribution expected for a soluble, cytosolic protein (22,23). This distribution leaves only 10 -15% of the Pdc in the outer segment (22,23), an amount that appears insufficient to sequester G t ␤␥ during an initial light response given that there are approximately equal amounts of G t and Pdc in the entire photoreceptor cell (23)(24)(25) and that G t is localized almost exclusively in the outer segment in the dark (26 -29), whereas Pdc distribution does not change in the light or dark (22,23). This notion was confirmed by data from the Pdc knock-out mouse that exhibited no change in initial photoresponse kinetics when compared with wild-type (23).…”
mentioning
confidence: 94%